Analysis of Judicial Decisions Imposing Sentences Below The Minimum Penalty Threshold in Article 112 Paragraph (1) of The Narcotics Law - Radha Rani, Ni Made Dwi; M.E. Purwani, Sagung Putri (Westscience Press, 2025)
This research analyzes the Decision of the Denpasar District Court Number 249/Pid.sus/2024/PN Dps, wherein the court imposed a sentence below the special minimum threshold as stipulated in Article 112 paragraph (1) of the Narcotics Law. Employing a normative juridical research methodology with a statutory approach, this study examines the legal considerations utilized by judges in rendering decisions below the minimum threshold and identifies the implications of such decisions on law enforcement and narcotics policy in Indonesia. The findings demonstrate that the judicial panel based its decision on Supreme Court Circular Letter (SEMA) Number 3 of 2015, considering that the defendant was proven to be a user and possessed a relatively small quantity of narcotics. This phenomenon of sentencing below the minimum threshold generates legal complexities in the form of legal uncertainty due to its contravention of the legality principle, the diminishment of deterrent effects, and the creation of inconsistency in judicial decisions that potentially undermines public confidence in the judiciary. This research recommends harmonization of legislation pertaining to narcotics offenses, development of more proportionate sentencing policies with a public health approach, and the necessity for a monitoring system regarding judicial decisions that deviate from special minimum provisions.